Catatonic Dilemma in a 33-Year-Old Woman: A Discussion - Koch, Alexander; Reich, Karin; Wielopolski, Jan; Clepce, Marion; Fischer, Marie; Kornhuber, Johannes; Thuerauf, Norbert (Case Reports in Psychiatry, 2013)
Case. We report a case of catatonia with elevated CK, elevated temperature, and hypoferritinemia after abrupt discontinuation of clozapine in a patient with known proneness to catatonic symptoms. Reinstatement of clozapine therapy was contraindicated due to leukopenia. Neuroleptic malign syndrome could not be ruled out by the administration of quetiapine; this prevented the quick use of other potent D2 antagonists. Some improvement was achieved through supportive therapy, high dose of lorazepam, and a series of 10 ECT sessions. Returning to baseline condition was achieved by a very careful increase of olanzapine. Discussion. Catatonic symptoms in schizophrenia as well as in NMS might be caused by a lack of striatal dopamine (CS) or dopamine D2 antagonism (NMS). CS might be a “special” kind of schizophrenia featuring both hypo- and hyperactivity of dopaminergic transmission. ECT has been described as a “psychic rectifier” or a “reset for the system.” The desirable effect of ECT in cases of CS might be dopaminergic stimulation in the striatum and decrease of both the dopaminergic activity in the limbic system and the serotonergic activity on 5-HT2 receptors. The desirable effect of ECT in NMS would be explained by activation of dopaminergic transmission and/or liberation of dopaminergic receptors from the causative neuroleptics.